QUALITY OF INFORMATION AS STRATEGIC FACTOR IN ACCOUNTING INFORMATION SYSTEM (AIS) TOWARDSBETTER ORGANIZATIONAL PERFORMANCE - Sami, Mohammed (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2011)
The aim of this study is to examine the information quality and its effect on performance of Iraqi companies. Organizations were found aware on the need to have quality of information as to cope with environmental uncertainty. Most organizations agree on the importance of accounting information system (AIS) as to gather, perform, and report about the performance of their financial activities. Findings show quality of information is an important factor for performance enhancement. Therefore, to become or remain competitive need organizations to have good AIS as it helps organizations to formulate better strategies and later achieve better organizational performance. This means quality of information is certainly a strategic factor for organizational survival or prosperity.